Analisis Kelimpahan Dinoflagellata Bentik Beracun di Perairan Teluk Bayur, Sumatera Barat - Vivin Seygita; Thamrin Thamrin; Yusni Ikhwan Siregar (Universitas Riau, 2015)
Epibenthic dinoflagellates are of important as primary producer in coastal and oceanecosystems. But it has potent toxins causing harmfull effect to marine fauna as well as to human.The present study aimed at analyzing the abundance of three genus ; Ostreopsis, Prorocentrumand Gambierdiscus in Teluk Bayur Bay, West Sumatera, which sampling were conducted inNovember 2014. Environmental parameters were including Nitrate, Phosphate concentration anddensity of Sargassum vegetations were measured which preasumably influence the dinoflagellatesabundance. Apparently, abundance of dinoflagellates ranged from 2061-7116 cells/g. Samplingstations had no effect on abundance of dinoflagellates. Water quality (N, P and Sargassumvegetation density) had no effect to the present and abundance of dinoflagellates, in all samplingstations.